Effect of Bank Diversification on the Financial Distress of Commercial Banks Listed at the Nairobi Securities Exchange, Kenya - Dr. Benedict Alala Ondiek, Innocent Masase Mochabo, Dr. Kennedy B. Mwengei Ombaba (International Journal of Scientific Research and Management (IJSRM), 2017)
Due to the dynamic environment, banks are always striving to achieve a competitive advantage. In this sense, they have identified different strategies for diversification in order to survive. The purpose of this study was to determine the effect of bank diversification on financial distress of commercial banks listed in the Nairobi Securities Exchange. The specific objective of the study was to determine the effect of geographical and asset base diversification on the financial distress of the listed commercial banks in the NSE. The theories that guided this study included market power theory, resource dependency theory and resource based view theory. Exploratory research design was used. The research targeted ten listed commercial banks in the NSE. This study used panel data of a ten years period (2006-2015) from the audited and published financial statements of commercial banks. Descriptive and inferential statistics was employed for data analysis. This study established that geographical diversification was positively and significantly correlated with financial distress (b=0.0065; p